Coral Reefs of India - Under Threat - Sankanur, Mahantappa; Saresh, N. V.; Somashekharaiah, S. L.; Verma, Archana; Bhat, S. D. (Indian Forester, 2012)
Importance of the Coral reefs and threats being faced by them are discussed in details. Steps have been enumerated to protect the coral eco-systems.